Ubezpieczenia ekologiczne jako instrument finansowy w ochronie środowiska - Rutkowska, Małgorzata; Kozyra, Przemysław (Ecological insurances as a financial instrument in the environment protection, 2007)
This paper shows chosen issues about ecological insurances - law analysis of through the question of under what conditions the insurance should be madę compulsory. The major argument in favour of compulsory liability insurance is insolvency of the potential perpetrator for ecological damage. This can be cured through making the purchase of insurance compulsory. However, if the morał hazard problem cannot be cured or if insurance is not sufflciently available, making insurance compulsory may create morę problems than it cures. In Poland so far, liability of the perpetrator responsible for ecological damage is only a theoretical discussion owing to ecological insurances aren’t generally present neither in companies nor in the insurance market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 460-469